A theory of auditability for allocation mechanisms - Aram Grigoryan; Markus Möller (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
In centralized mechanisms and platforms, participants do not fully observe each others' type reports. Hence, if there is a deviation from the promised mechanism, participants may be unable to detect it. We formalize a notion of auditabilty that captures how easy or hard it is to detect deviations from a mechanism. We find a stark contrast between the auditabilities of prominent mechanisms. We also provide tight characterizations of maximally auditable classes of allocation mechanisms.
Keywords: D47; D80; 330; Auditability; Allocation Mechanisms